Gestational Diabetes Mellitus Changes Human Colostrum Immune Composition - Avellar, Ana Carolina de Sena; Oliveira, Mariana Naves; Caixeta, Felipe; Souza, Rafaela Cristina Vieira e; Teixeira, Andréa; Faria, Ana Maria Caetano; Silveira-Nunes, Gabriela; Faria, Elaine Spezialli; Maioli, Tatiani Uceli (Frontiers in Immunology, 2022)
Abstract Breast milk is considered a complete food for the baby. Up to 7 days postpartum, it is known as colostrum, rich in immunological compounds, responsible for providing nutrition and ensuring immune protection. However, some maternal factors, such as Gestational Diabetes Mellitus (GDM), can change the concentration of bioactive compounds present in colostrum and may affect the development of the newborn’s immune systems. The effect of GDM on colostrum cytokine, chemokine, and growth factors is not well described. So, the present study evaluated whether the occurrence of GDM changes the concentration of biomarkers in colostrum. A cross-sectional study was carried out with postpartum women who had healthy pregnancies and women who had been diagnosed with GDM. A sample of colostrum was collected for Luminex analysis. Our results showed that GDM mothers had more secretion of cytokines and chemokines in the colostrum, with a higher concentration of IFN-g, IL-6, and IL-15, and less concentration of IL-1ra. Among growth factors, we identified a decreased concentration of GM-CSF in the colostrum of GDM mothers. So, the data obtained support the idea that the disease leads to immune alterations in colostrum.